Perancangan Sistem Informasi Pengadaan Barang Berbasis Web (Studi Kasus : CV. Royal Transindo) - Gilliani, Wenny; Errissya Rasywir; Lazuardi Yudha pradana (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
Royal Transindo is a company engaged in the procurement of goods related to employment needs. Currently the company still uses Microsoft Word and Microsoft Excel which are still commonly used. Every goods procurement activity is made by the administrator and managed by the owner, which is still less effective and requires a long time and there are delays in identifying data information such as selling prices, goods specifications and so on to customers. Therefore, based on existing problems, the author will design and create a goods procurement information system on CV. Royal Trasindo. This research was built using the PHP programming language and MySQL DBMS. Apart from that, we also apply the Agile Software Development method using the UML (Unified Modeling Language) method by creating various kinds of system modeling such as Use Case Diagrams, Activity Diagrams, Class Diagrams and Flowchart Diagrams. With this information system, it is hoped that it will make it easier for system users, both administrators and company owners, to reduce delays in providing data information such as selling prices, product specifications and so on to customers. Apart from that, this web-based system can reduce the risk of losing data that the company does not want and it is hoped that the system built can produce good computerized reports to make it easier to calculate profit/loss.